2023
DOI: 10.1021/acs.analchem.2c05613
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic Sweat Wearable Uric Acid Sensor Based on N-Doped Reduced Graphene Oxide/Au Dual Aerogels

Abstract: Sweat wearable sensors enable noninvasive and real-time metabolite monitoring in human health management but lack accuracy and wearable applicability. The rational design of sensing electrode materials will be critical yet challenging. Herein, we report a dual aerogel-based nonenzymatic wearable sensor for the sensitive and selective detection of uric acid (UA) in human sweat. The three-dimensional porous dual-structural aerogels composed of Au nanowires and N-doped graphene nanosheets (noted as N-rGO/Au DAs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…As the oxidation proceeds for 30 min, the peak intensity of −C�N− vibration continuously increases, leading to a decrease in oxidation current in CV measurement due to the adsorption of dehydrourate on PyTS@Ti 3 C 2 T x modified electrode surface. 9 Therefore, both electrochemical and spectroscopic results provide evidence that two hydrogen atoms are removed from uric acid molecules to form dehydrourate through nonenzymatic electrochemical oxidation of UA. PyTS@Ti 3 C 2 T x -Based Wearable Sensor Monitoring of Sweat UA.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the oxidation proceeds for 30 min, the peak intensity of −C�N− vibration continuously increases, leading to a decrease in oxidation current in CV measurement due to the adsorption of dehydrourate on PyTS@Ti 3 C 2 T x modified electrode surface. 9 Therefore, both electrochemical and spectroscopic results provide evidence that two hydrogen atoms are removed from uric acid molecules to form dehydrourate through nonenzymatic electrochemical oxidation of UA. PyTS@Ti 3 C 2 T x -Based Wearable Sensor Monitoring of Sweat UA.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Previous research has demonstrated a significant correlation between the concentration of UA in blood and sweat . Measurement of UA concentration in sweat is a challenge due to its low concentrations (2–200 μM) . The currently employed sweat-based electrochemical wearable sensors have been utilized for the monitoring of dynamic health and personalized intervention. However, enzyme-based sensors have encountered challenges in terms of the limited stability, lack of reproducibility, pH and temperature dependence, reactive enzyme immobilization and the complicated preparation process of the natural enzymes bring to the high cost. , Therefore, the ongoing advancement in utilizing innovative nanomaterials as sensitive materials for integration into sensors to achieve stable, selective, and highly sensitive detection of target molecules, instead of the enzymatic reaction, remains an active area of research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nyein et al developed wearable patches to detect resting sweat pH, Cl – , and l -dopamine for continuous and autonomous monitoring of body physiology at rest; Zhao et al analyzed stress biomarkers (cortisol, Mg 2+ , and pH) in resting sweat by integrating a wearable sweat sensing patch for diagnostic studies of psychological stress; Saha et al developed a lactate transient sensor under low sweat secretion to continuously monitor sweat lactate changes. Similarly, the increase of the sweat uric acid (UA) level is related to the occurrence and progression of metabolic syndrome, obesity, diabetes, coronary heart disease, and other diseases. , However, most of the current wearable sensors for UA detection are tested in exercise sweat, and there is a lack of sensors that can detect UA in resting sweat.…”
Section: Introductionmentioning
confidence: 99%
“…Aerogels are solid three-dimensional networks with pores filled with air. , The unique structures of aerogels endow them with extremely low density, high porosity, and large surface area, which have enabled their potential application in the fields of thermal insulation, catalysis, sensing, optoelectronics, environmental remediation, electromagnetic interference shielding, and energy storage and conversion. Among all types of aerogels, silica aerogels are so far the most studied ones due to their practical usage as thermal insulation materials in buildings and industry, catalyst supports, and adsorbents for oil spill cleanup. Silica aerogels are conventionally produced by a sol–gel method involving the steps of hydrolysis, condensation, aging, solvent-exchanging, and supercritical drying (Figure S1). This multistep method is sophisticated and time-consuming and sometimes requires expensive molecular precursors, leading to the high cost of production.…”
Section: Introductionmentioning
confidence: 99%